Role of Wrist Arthroscopy in Juvenile Inflammatory Arthritis - Ishwar, Mahalakshmi; Lindau, Tommy R.; Johnson, Karl; Pidgeon, Claire; Jester, Andrea; Coles, William; Oestreich, Kerstin (Journal of Wrist Surgery, 2022)
Background and Purposes The wrist is the fourth most common joint to be involved in juvenile inflammatory arthritis (JIA), which is a common rheumatological condition affecting children. Wrist arthroscopy is well established in rheumatoid arthritis, but remains unexplored in JIA. The aim of this study is to investigate the role of wrist arthroscopy in JIA, with focus on those who are refractory to medical management.Methods This is a prospective observational study, including consecutive patients with JIA undergoing arthroscopy between January 2016 and December 2020. Those over the age of 18 years and those with other rheumatological diagnoses were excluded. Data including pre-, intra-, and postoperative variables, demographics, and patient-reported outcomes were collated and are reported using standard measures.Results A total of 15 patients underwent arthroscopy (n = 20 wrists). Synovitis was noted in all wrists on arthroscopy and synovectomy was performed in all cases. Other procedures were performed as indicated during the procedure. The median follow-up duration was 11.3 (interquartile range [IQR] 8.1–24.2) months. Median reduction of 4 (IQR 2.25–6) points on the Visual Analogue Score for pain on loading was noted postoperatively. Grip strength was improved in n = 11/20 wrists and functional improvement was noted in n = 18/20 wrists. Restriction of range of motion was achieved with a shrinkage procedure in patients with hypermobile joints. There were no postoperative complications, and no patients were lost to follow-up.Conclusion In experienced hands, wrist arthroscopy is feasible, safe, and efficacious in the management of JIA, among patients who are refractory to medical management.Level of Evidence This is a Level II study.
Keywords: wrist; arthroscopy; juvenile inflammatory arthritis; pain; synovitis; synovectomy; range of motion